The Game of Skittles on the Northern Route of the Camino de Santiago - Rodríguez-Fernández, José E.; Lorenzo-Moledo, Mar; García-Álvarez, Jesús; Míguez-Salina, Gabriela (Frontiers in Psychology, 2020)
The main purpose of this study is to discover and record information related to the game of skittles throughout the northern route of the Camino de Santiago, considering its current practice, modalities, practice places and its different manifestations as an informal and formal game (sport), making comparisons with other traditional playful practices located on this pilgrimage route. A mixed qualitative-quantitative study was designed in which 89 people (municipal technicians, politicians, players, club managers and teachers) participated, constituting an informant for each municipality where the Northern Camino passes. An ad hoc questionnaire was used for the data collection, which was processed through content analysis by expert judges (qualitative section) and with the IBM-SPSS statistical package (version 25). The results of the research shows an important skittles activity on the Northern Camino (58.32% of the municipalities), reflected in the number of registered playing fields (n = 291), the number of clubs, associations and peñas that participate in federated leagues (n = 162) and the wide variety of skittles modalities currently present on the Camino (n = 20). The relationship between skittles and local culture, symbols of identity of these regions of northern Spain, made possible the inheritance of traditions in these places keeping them still alive, despite the push of new playful trends and most attractive and innovative sports.